The role of intestinal microbiota and its metabolites in the occurrence and intervention of obesity - Gao, Yang; Liu, Wenhui; Ma, Xue; Xue, Min; Li, Yingying; Bi, Shanshan; Leng, Huan (Frontiers in Microbiology, 2025)
Obesity is a growing global health challenge influenced by genetic and environmental factors. With economic development, obesity rates continue to rise globally. Recent research highlights the critical role of gut microbiota in obesity pathogenesis, particularly through microbial metabolites affecting metabolism and energy homeostasis. Recent studies indicate that gut microbiota significantly influences obesity development through metabolic interactions, including the regulation of glucose and lipid metabolism. Gut microbiota is involved in the metabolism of various nutrients such as glucose and lipids, and the change of gut microbiota leads to insulin resistance, adipose tissue accumulation and metabolic disorders, thus mediating the occurrence and development of metabolic diseases. For example, beneficial bacteria such as Bifidobacterium and Lactobacillus, which are in high abundance in animal intestinal tract, can prevent obesity by enhancing the intestinal barrier, improving insulin sensitivity and improving metabolic disorders. Many of these effects are mediated by metabolites produced by intestinal microbiota, such as short-chain fatty acids, which play an important role in preventing and treating obesity. In this research review, we used the PubMed database and Google Scholar and web of science to search for relevant literature within recent 20 years on the topic of microbes and microbial metabolites in relation to obesity. Key words used were obesity, metabolic diseases, gut microbiota, metabolic disorders, gut microbial metabolites to search for references. The purpose of this review article was to describe the current knowledge on the impact of gut microbiota and their metabolites on obesity, in order to provide a more comprehensive understanding of the relationship between gut microbiota and obesity for future clinical intervention and prevention of obesity.